New approaches to the classification of causes of aviation accidents and incidents as an effective means of improving safety - Луппо, O.Є.; Алєксєєв, О.М. (Proceedings of National Aviation University, 2007)
Classification of accidents and incidents makes principle of hieratic collateral subordination, which determines separate classification of direct and main reasons that enables to estimate weight destiny of every structure in the decline of safety flight and expose most bottleneck in the aviation system. Exposure of main reasons and frequency of their repetition, for a concrete period, allows to define the role of each components in the decline of safety of flights and estimate efficiency of the before developed prophylactic measures from warning of the same type aviation events and incidents in a future.